Aspectos socioecômicos da produção e percepção ambiental dos catadores de Caranguejo-Uçá Ucides Cordatus (Linnaeus, 1763) da comunidade do Treme, Bragança-PA - COUTO, Renata Louzada do (2019)
For the crab pickers, the crab-uçá is the most important fishing resource from the mangroves. The crab processing and marketing activity generates monetary income for more than half the rural households in the region of Bragança. In view of this importance, the objective of this study is to characterize the crab-uçá catch process, as well as to outline the socioeconomic profile of the crab collector of the Treme community, Bragança-PA, and to record their environmental perception in relation to bioecology of the crab-uçá, to the mangrove and to the legal devices that guide the capture activity. For this, 30 interviews were carried out using a structured questionnaire, consisting of open and closed questions that addressed the social aspects of the collectors, the ways of catching and marketing the resource, and their knowledge about the bioecology of the species and the closed period. With the characterization of the productive dynamics of the activity, it is expected that the obtained data can help in the evaluation of the socio-environmental sustainability of the activity, social and economic factors that may be interfering in the management processes of this natural resource, besides being able to contribute to a monitoring of long-term planning of such extractive activities.